2007
DOI: 10.1007/bf03033917
|View full text |Cite
|
Sign up to set email alerts
|

Changes in open-field activity and novelty-seeking behavior in periadolescent rats neonatally treated with monosodium glutamate

Abstract: Monosodium glutamate (MSG) treatment of neonatal rodents leads to degeneration of the neurons in the arcuate nucleus, inner retinal layers and various other brain areas. It also causes various changes in the motor activity, sensory performance and learning abilities. We have previously shown that MSG treatment delays the appearance of some reflexes during neurobehavioral development and leads to temporary changes in reflex performance and motor coordination. Investigation of novelty-seeking behavior is of grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 56 publications
1
27
0
2
Order By: Relevance
“…This excitotoxicity has shown to be most severe in the retina, in the cortex, and in the hippocampus [82, 8588]. Moreover, glutamate excitotoxicity has also been previously linked to neurobehavioral delays [82, 85]. Interestingly, the biochemical findings of this study showed that both Grx2 and Trx1 acted in the biomarker reduction associated with the glutamate excitotoxicity pathway which was increased after hypoxia/ischemia (Figure 2).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…This excitotoxicity has shown to be most severe in the retina, in the cortex, and in the hippocampus [82, 8588]. Moreover, glutamate excitotoxicity has also been previously linked to neurobehavioral delays [82, 85]. Interestingly, the biochemical findings of this study showed that both Grx2 and Trx1 acted in the biomarker reduction associated with the glutamate excitotoxicity pathway which was increased after hypoxia/ischemia (Figure 2).…”
Section: Discussionmentioning
confidence: 54%
“…During this period, different insults, such as a hypoxic/ischemic event, can affect the normal development of those reflexes and physical skills [30, 8284]. Previous studies have shown that glutamate neurotoxicity plays a key role in the impairment of the development of neurological reflexes and motor skills [82, 85]. This excitotoxicity has shown to be most severe in the retina, in the cortex, and in the hippocampus [82, 8588].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the neuroprotective function of AA ameliorates MSG-induced cognitive deficits in vivo. The neonatal administration of MSG causes cognitive deficits in adult animals [50][51][52] . The Morris water maze is a commonly used method for evaluating learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Parameters measured include: ambulation (number of squares crossed), rearing (both forepaws leave the ground), grooming behavior, head lifting (lifting the head and neck in an exploratory manner) and defecation [19,22].…”
Section: Open Field Behaviormentioning
confidence: 99%